Autonomic recovery during high training loads in female world-class biathlon athletes - Emanuelsen, E. (2009)
Purpose: This study aimed to investigate the relationship between resting heart rate (HRrest), heart rate variability (HRV), training impulse (TRIMP), and self-rated fatigue during three weeks of competitive training in female world-class biathlon athletes. Methods: Seven female world-class biathlon athletes were monitored during a high volume (long-distance) training period (DIST), an intensive competition training period (INT), and a moderate training period (MOD). The athletes performed 5 min supine HRrest and HRV measurements by use of Polar RS800 heart rate monitors every morning, and self-rated fatigue was recorded every evening by use of a fatigue scale. Training was recorded in training diaries based on HR recordings. After a validation study, comparing Polar measurements with ECG, the HRV results were excluded from the further analysis. Results: Resting heart rate increased significantly during DIST and INT, as compared to MOD. No correlations between HRrest, TRIMP and self-rated fatigue were found. Inter-individual cross correlations showed no significant relationships between HRrest and TRIMP. Conclusion: The significant relationship between HRrest and TRIMP shows that female world-class biathlon athletes are autonomic affected by periods of extremely high training loads and by high intensity competition periods. However, a moderate training period leads to a reduced HRrest, indicating an autonomic recovery. The individual variations in HRrest during the three training periods indicate an individual influence by different types of training loads.